The evaluation of mean platelet volume levels in patients with idiopathic and ischemic cardiomyopathy: an observational study - AÇIKGÖZ, NUSRET; Acikgoz, Nusret; ÖZDEMİR, RAMAZAN; ERMİŞ, NECİP; Yagmur, Julide; CANSEL, MEHMET; Atas, Halil; PEKDEMİR, HASAN; ÖZDEMİR, Ramazan (My University, 2011)
Objective: Cardiomyopathy (CMP) is a disorder associated with an increased risk of thromboembolism due to blood stasis, platelet activation and altered coagulation status. In this study, we aimed to investigate mean platelet volume (MPV) in patients with idiopathic CMP and ischemic CMP and to compare with those of the controls, and aimed to determine whether there is a relationship between MVP and echocardiographic parameters in patients with CMP.